Theoretical and legal aspects of compulsory deprivation of property rights - Suindikov, N.M. (Bulletin of the Karaganda University “Law Series”, 2025)
The aim of the study is to conduct a comprehensive theoretical and legal analysis of the institution of compulsory deprivation of property rights in the legislation of the Republic of Kazakhstan, taking into account the amendments introduced by the Law ‘On the Return of Illegally Acquired Assets to the State’. Special attention is given to identifying the essence of this institution, its place in the system of civil law mechanisms for terminating ownership rights, and assessing the balance between constitutional guarantees of property rights and the public interests of the state. The study analyses the provisions of the Constitution of the Republic of Kazakhstan, the Civil Code and the aforementioned Law, as well as international experience from countries with continental and Anglo-American legal systems. It is shown that the Kazakh model combines features of both legal traditions, including the application of a reduced standard of proof (‘reasonable degree of certainty’) and the redistribution of the burden of proof between the plaintiff and the defendant. It is noted that this approach contributes to the effectiveness of procedures for the return of assets of unexplained origin, but requires more detailed regulation of the concepts used. The results of the study indicate the heterogeneity of the institution of compulsory deprivation of property rights: some forms of it involve compensation (requisition, seizure for public use), while others exclude it entirely (confiscation, conversion of assets of illegal origin into state revenue). This approach reflects the balance between protecting private rights and the need to ensure the rule of law and the interests of society. It is concluded that further development of the institution of compulsory deprivation of property in Kazakhstan should be linked to the formation of uniform judicial practice, clarification of the criteria for ‘reasonable degree of certainty’ and ensuring the proportionality of state intervention in property rights, which will strengthen confidence in the legal system and increase the effectiveness of asset recovery.